The Percentage of the Contribution of the Conceptual Fluency with the Accuracy of Some Offensive Technical Skills in Volleyball Original Scientific Paper - Walid, Muhammad; Uday Abdul-Hussein,; Hameed, Basim Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
The conceptual fluency of the educated student in the academic stage is of great importance because his main dependence on some simple information but it gives very important information for the repeated moves in the performance of offensive skills because the lack of good planning gives great opportunities to the defending team to resolve the moves that can be invested in the team's harvest of many points, And the research community was identified represented by the fourth stage students in the College of Physical Education and Sports Science - Diyala University for the academic year (2017-2018) and by (5) people and its people were excluded (and) being a female students section and the research sample was chosen in a random, unorganized way which is the path of The lottery By (5) people, whose number is (30) students for the main experiment, it represents (27%), and (10) students for the exploratory experience at a rate of (9%) of the original research community of (111), which represents (100%) The results showed that there were significant associations as well as a contribution of (49%) and the rest (51%) due to other factors.